The Influence Of Work Life Balance And Emotional Intelligence On Employee Performance With Job Satisfaction As A Mediating Variable At PT. Central Sandang Jayatama Cilacap - Basalamah, Laila; Kharismasyah, Alfato Yusnar; Hengky Widhiandono; Arini Hidayah (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This resesearch aims to examine the relationship between the variables Work Life Balance, Emotional Intelligence, Job Satisfaction, and Employee Performance. The mediating role of Job Satisfaction is used to analyze the indirect influence between variables. Respondents in this resesearch were permanent employees at PT Central Sandang Jayatama Cilacap. The sampling technique was applied to a population of 800 employees at PT. Central Sandang Jayatama Cilacap. The sample size was initially determined using Slovin’s formula with a 10% margin of error, resulting in 89 respondents. To enhance the validity and representativeness of the data, the sample size was subsequently increased to 150 respondents. The data were processed and analyzed using the SmartPLS software. A quantitative approach was chosen to explain the causal relationship between variables. The results of the resesearch showed that Work Life Balance had no significant effect on employee performance, Emotional Intelligence had a positive and significant effect on employee performance, Work Life Balance and Emotional Intelligence had a positive and significant effect on Job Satisfaction, job satisfaction had a positive and significant effect on employee performance and Work Life Balance and Emotional Intelligence had a significant effect on Employee Performance through the mediation of Job Satisfaction. This resesearch contributes by including the variable Job Satisfaction as a mediator between Work Life Balance, Emotional Intelligence, and Employee Performance.